Anatomical Study of the Epidermis Leaves and Stems of Melilotus Mill. and Scorpiurus L. Genera Species (Leguminosae) in Iraq - Al-Lami S. H. B.; Al-Shammary W. I. J. (Al-Qadisiyah Journal of Pure Science, 2018)
The current research was conducted anatomical study of the epidermis leaves and stems of Melilotus Mill. and Scorpiurus L. genera species in Iraq, which included four species (M. alba, M. indica, M. messanensis and M. officinalis) of the first genus and one species is two variety (S. muricatus var. muricatus and S. muricatus var. subvillosus) to second genus.Studied the anatomical characteristics to epidermis of leaves and stems to species of genera under study, included ordinary epidermis cells and stomatal complex to leaves and stems increased the important qualities in diagnosis.